Low inflation and monetary policy in the euro area - Antonio M. Conti; Stefano Neri; Andrea Nobili (European Central Bank (ECB), 2017)
Inflation in the euro area has been falling since mid-2013, turned negative at the end of 2014 and remained below target thereafter. This paper employs a Bayesian VAR to quantify the contribution of a set of structural shocks, identified by means of sign restrictions, to inflation and economic activity. Shocks to oil supply do not tell the full story about the disinflation that started in 2013, as both aggregate demand and monetary policy shocks also played an important role. The lower bound to policy rates turned the European Central Bank (ECB) conventional monetary policy de facto contractionary. A country analysis confirms that the negative effects of oil supply and monetary policy shocks on inflation was widespread, albeit with different intensity across countries. The ECB unconventional measures since 2014 contributed to raising inflation and economic activity in all the countries. All in all, our analysis confirms the appropriateness of the ECB asset purchase programme.
Keywords: C32; E31; E32; E52; 330; Bayesian methods; inflation; monetary policy; oil supply; VAR models